Environmental Degradation: Issues and Determinants in Middle-Income Countries ASEAN - Amar, Syamsul; ., Ariusni; Satrianto, Alpon; Ikhsan, Akmil (Journal of Ecohumanism, 2024)
This study is aimed at analyzing the impact of foreign direct investment, foreign debts, consumption of fossil fuel, corruption, political stability and net-export on environmental degradation, poverty and economic growth in middle-income countries in ASEAN. The method applied is simultaneous equation analysis by taking into account classical assumption tests such as granger causality and heteroskedasticity. The Data started during the years 2010-2023 in middle-income countries in ASEAN. Poverty, economic growth, foreign direct investment, fossil fuel consumption have a significant effect on environmental degradation. Environmental degradation, economic growth, foreign debt, have a significant effect on poverty. Environmental degradation, poverty and net export on economic growth of ASEAN middle-income countries. The government and related parties need to focus on controlling environmental impacts, reducing poverty, and managing inclusive economic growth through a sustainable approach.